On a new species of the genus Simlops (Araneae, Oonopidae) from Guyana, with notes on the bodanus group of species - Feitosa, Níthomas M. (Museu Paraense Emilio Goeldi, 2018)
A new species of Simlops Bonaldo, Ott & Ruiz, 2014, S. kartabo sp. nov., from Guyana is described. The new species belongs to the putatively basal bodanus species group, sharing with other species of the group a relatively simple embolar distal third. The presence of a fi liform accessory process on the conductor, previously evidenced only for S. guatopo Brescovit, 2014 is also identifi ed here for S. bodanus (Chickering, 1968), S. guyanensis Santos, 2014 and S. kartabo sp. nov. and may support the monophyly of the bodanus group.